Yachts Passing by the West Coast of Portugal – What to Do to Make the Marina and the Destination of Figueira da Foz a Nautical Tourism Reference? - Silveira, Luís Eduardo Ávila Da (2018)
Yachting appears as a tourism segment with proven and specific importance for the economic and social development of tourist destinations Every year, thousands of yachts cross the Portuguese waters. Figueira da Foz is a seaside city and a destination with a history connected to tourism activities. Despite having a marina located in the city centre, the number of yachts stopping by is still far from this nautical port maximum capacity. As a reaction, and to change this reality, both local and regional stakeholders have participated in a Delphi panel to find out if yacht tourism has the potential to increase. It has been found that both the destination and its marina have the resources to attract and make this territory a nautical reference, and a strategy has been created. This model may serve as a basis for application in other nautical ports.